Analisis Bauran Pemasaran dan Harga Pokok Produksi (HPP) Produk Pisang Goreng Beku pada Agroindustri Pisang Goreng Beku Shamiya - Anisyara Olyvia, Dinda; Aring Hepiana Lestari, Dyah; Nugraha, Adia (Politeknik Negeri Lampung, 2023)
This study aims to analyze the marketing mix’s application and production cost in the frozen fried banana agroindustry. The research applies the basic case study method taken at the Shamiya Frozen Fried Banana Agroindustry in Kedaton District, Bandar Lampung. The location was determined purposively through the initial consideration that this agroindustry was the first frozen fried banana producer in Bandar Lampung. Owners and employees of agro-industry and consumers of frozen fried bananas, Shamiya, were appointed as research respondents. Samples were collected using accidental sampling technique. The number of samples is 30 household consumers who consume Shamiya frozen fried bananas. Data was collected during December 2021 - February 2022. Marketing mix analysis was determined as data analysis through the perspective of agro-industry owners and consumers' perspectives and analysis of the cost of production using the full costing method. Based on the owner’s perspective, the results showed that the Shamiya frozen fried banana agroindustry had implemented the marketing mix components well. Based on the consumer's perspective, Shamiya's frozen fried banana agroindustry has also implemented the marketing mix components well. The calculation of the cost of production shows that the Shamiya frozen fried banana agro-industry benefits from the five products by an average of 144.24 percent of the current selling price, because the selling price is set above the cost of production.